Shaking Table Test on Dynamic Response of Bedding Rock Slopes With Weak Structural Plane Under Earthquake - Yang, Changwei; Zhang, Liang; Liu, Yang; Tian, Denghang; Guo, Xueyan; Liu, Yang (Frontiers in Physics, 2020)
Taking a bedding rock slope with weak structural plane as the prototype, a shaking table test with a similarity ratio of 1:10 is designed and carried out. By analyzing the acceleration and displacement responses at different positions of the slope, the seismic response and instability mechanism of rock bedding slope under different seismic amplitudes, frequencies, and durations are studied. Before the failure of the slope, the rock bedding slope shows an obvious “elevation effect” and “surface effect” under the action of Wenchuan Wolong earthquake wave with different amplitudes. With the increase of the amplitude of the input seismic wave, the elevation effect and the surface effect gradually weaken. When the amplitude of the seismic wave reaches 0.9 g, the rock bedding slope begins to show damage, which demonstrates that the difference of PGA amplification coefficients on both sides of the weak structural plane increases significantly. Compared with the Kobe seismic wave and Wenchuan Wolong seismic wave, the excellent frequency of EL Centro seismic wave is closer to the first-order natural frequency of slope model and produces resonance phenomenon, which leads to the elevation effect of PGA amplification coefficient more significantly. Through the analysis of the instability process of rock bedding slope, it can be found that the failure mechanism of the slope can be divided into two stages: the formation of sliding shear plane and the overall instability of the slope.